Astor Piazzolla’s compositional and interpretive styling of his Tango Adiós Nonino across four decades of his career – insights into the emergence of Nuevo Tango - Gina-Mihaela Pavel (Cogent Arts & Humanities)
Argentinian musician Astor Piazzolla is best known and celebrated for reinventing traditional Argentinian tango as Nuevo Tango by inviting jazz and classical influences into his compositions and performances. Written to honor his father, Adiós Nonino held a special place in Piazzolla’s heart and repertoire. His own interpretations of Adiós Nonino in various arrangements illustrate the evolution of his style from traditional to experimental and innovative. This study is a comparative analysis of nine recorded performances of Adiós Nonino featuring Astor Piazzolla himself as lead bandoneonist, dated 1955, 1961, 1969, 1972, 1974, 1977, 1983, 1985 and 1989. Compositional structure, rhythmic and melodic motifs, distinctive techniques (fraseo, golpe de gaja), instrument arrangements, collaboration formats are reviewed. The most ‘revolutionary’ versions are arguably those arranged for and performed by Quintets from 1969 to 1983, the Conjunto 9 nonet from 1972, the electronic Octets from 1976 to 1977, and the orchestral version from 1985. Piazzolla’s style and the emergence of Nuevo Tango owes a great deal to his open collaborations with musicians of different backgrounds, approaching tango from classical, jazz, and even rock music perspectives. Finally, the potential for further comparative analyses of musical pieces by Astor Piazzolla and other musicians is explored.